Contemporary challenges of participatory field research for land use change analyses: examples from Kenya - Smucker, T.; Campbell, D.J.; Olson, J.; Wangui, Elizabeth Edna (SAGE Publications, 2007)
This article discusses the evolution of participatory methods and their benefits and pitfalls in contributing to land use and land cover change (LULCC) analyses. Participation has become a practical means of developing a more complete assessment of societal change by bringing local people’s narratives and understandings to bear on the interpretation of data collected using more extractive methods, such as the household survey, or data collected remotely, such as satellite images. Their methodological value lies in their ability to provide insights into the local mediation of external political, economic, and cultural processes. However, the realization of these contributions to LULCC analysis requires sensitivity to community differentiation, competing narratives of change, and the broader social context in which participatory forums take place. Examples from Kenya suggest that participatory feedback workshops present distinct empirical advantages that allow researchers to develop an understanding of critical intersections of social and environmental change through a dialogical process whereby participants themselves frame the central categories and change processes.